Pautas culturales de crianza familiar y desarrollo personal de los niños con autismo del distrito de Víctor Larco Herrera 2022 - Llontop Montenegro, Kevin Steve (2022)
The purpose of this research is to make known and articulate the essential aspects of the parentingguidelines that parents provide towards their children with autism, one of the most important pointsof this research is to identify the motivation, support and emotional affection remarkably in the personal development of their children with autism. The coexistence in the home of an infant with autism is usually very complex and families are subjected from the beginning to severe modifications of their habitual life regimen with excessivelimitations of their independence, since it is worth remembering that the upbringing guidelines infamilies with autistic children, they are not recipes that are proportionally established by an authoror famous person, but must be adapted to the needs of each autistic child. Many parents, despite their immense love and care for their children, are quickly bewildered by their lack of language, or by marked patterns of inflexibility, difficulty adapting to situations, disinterest in play or physical contact.